2016
DOI: 10.1371/journal.pone.0162369
|View full text |Cite
|
Sign up to set email alerts
|

National Outbreak of Multidrug Resistant Salmonella Heidelberg Infections Linked to a Single Poultry Company

Abstract: ImportanceThis large outbreak of foodborne salmonellosis demonstrated the complexity of investigating outbreaks linked to poultry products. The outbreak also highlighted the importance of efforts to strengthen food safety policies related to Salmonella in chicken parts and has implications for future changes within the poultry industry.ObjectiveTo investigate a large multistate outbreak of multidrug resistant Salmonella Heidelberg infections.DesignEpidemiologic and laboratory investigations of patients infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 10 publications
1
75
0
4
Order By: Relevance
“…Overall, the data indicated that isolate pairs from the same strain were not necessarily highly related. This is not surprising, as the outbreak involved multiple processing establishments, which were in turn sourced from multiple farms (28,29 (39). This makes JF6X01.0045 isolates unusually dissimilar for isolates from the same strain FIG 9 Differences in expression of genes encoding antibiotic resistance genes and multidrug efflux pumps during stationary phase at 37°C for each isolate compared to SL476 gene expression levels at the same temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the data indicated that isolate pairs from the same strain were not necessarily highly related. This is not surprising, as the outbreak involved multiple processing establishments, which were in turn sourced from multiple farms (28,29 (39). This makes JF6X01.0045 isolates unusually dissimilar for isolates from the same strain FIG 9 Differences in expression of genes encoding antibiotic resistance genes and multidrug efflux pumps during stationary phase at 37°C for each isolate compared to SL476 gene expression levels at the same temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The heat tolerance of SL476 was similar to that found in published data for Salmonella Enteritidis, but with more extreme tailing of the survival curve (15,47,48), while Salmonella Typhimurium ATCC 14028 had a somewhat lower heat tolerance than SL476 (not statistically significant). R1-0006 and R1-0003 were from strain JF6X01.0258, a strain that caused 186/634 outbreak illnesses, yet represented less than 1% of the Salmonella Heidelberg isolates in PulseNet prior to the start of the outbreak (28). This strain was also associated with illnesses from rotisserie chicken (28).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the Centers for Disease Control and Prevention reported that annually there are one million cases of salmonellosis in the USA [8]. Even though several food items such as peanuts [9], beef [10], pork [8] and chicken [11] have been associated with outbreaks of salmonellosis, the primary cause is raw eggs and egg products [12,13]. According to Painter [12], in the United States from 1998 to 2008, 57% of S. Enteritidis outbreaks were linked to food products prepared using eggs.…”
Section: Is Decontamination Of Eggs Essential?mentioning
confidence: 99%
“…Heidelberg in the United States. According to the CDC reports, five of these outbreaks were traced back to either chicken or turkey related products as the source of infection [13][14][15][16][17][18][19][20][21]. However, a very recent multistate outbreak caused by this serovar has been linked to contact with calves as the source of infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies on Salmonella ser. Heidelberg have mostly focused on outbreaks associated with poultry products [23][24][25][26][27]. Most of these analyses were carried out with a limited number of isolates from a small geographical region with a limited number of strains.…”
Section: Introductionmentioning
confidence: 99%